2019
DOI: 10.4314/gjpas.v25i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric study of the cranial parameters using Computed Tomography (CT) scan to establish cephalic index of a sampled population in Calabar, Nigeria

Abstract: Background: Ethnic characteristics of individuals are best described with the skull. Cranial index is one of the most important variables for determining sexual dimorphism and of course racial differences. Parameters used in establishing cephalic index vary considerably depending on the age, sex, geographical habitat, ethnic background of the individuals involved and the methods employed. Such has not been documented in Calabar, especially with the use of advanced imaging modality such as the Computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Similarly, the mean and SD values of FOD, BPD and CI were respectively found to be 170 ± 10.69, 122 ± 7.47 and 72 ± 5.67. This also agrees with many studies conducted in our locality (Omotoso et al, 2019;Udo-Affah et al, 2021) and across the globe at large, however, among healthy subjects (Omotoso et al, 2019;Paulinus et al, 2019). Unlike in many studies (Golalipour et al, 2005;Fawehinmi et al, 2009;Bernhardt et al, 2017), which were conducted on healthy subjects, the present study was among stroke patients and there was no similar study found or done in this locality, where stroke patients' head types were assessed, however, the findings of the present study agree with the studies mentioned above (Omotoso et al, 2019;Udo-Affah et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the mean and SD values of FOD, BPD and CI were respectively found to be 170 ± 10.69, 122 ± 7.47 and 72 ± 5.67. This also agrees with many studies conducted in our locality (Omotoso et al, 2019;Udo-Affah et al, 2021) and across the globe at large, however, among healthy subjects (Omotoso et al, 2019;Paulinus et al, 2019). Unlike in many studies (Golalipour et al, 2005;Fawehinmi et al, 2009;Bernhardt et al, 2017), which were conducted on healthy subjects, the present study was among stroke patients and there was no similar study found or done in this locality, where stroke patients' head types were assessed, however, the findings of the present study agree with the studies mentioned above (Omotoso et al, 2019;Udo-Affah et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The socio-demographic characteristics including the age and sex obtained from the present study (Table 1) were taken into consideration with respect to the cranial dimensions or parameters of the North India sampled population. On the gender distribution, results of our study showed no significant difference between females and males which corroborates similar work done by Ekizoglu et al [14], on the evaluation of gender in the modern Turkish population through the cranial CT anthropometric parameters, and Paulinus et al [15], also observed the same by cranial CT-anthropometric parameters over Nigerians residing in Calabar.…”
Section: Discussionsupporting
confidence: 91%
“…We performed a cross-sectional study on 1000 subjects. Akinbami [16] performed a cross-sectional study on the 700 subjects; Singh and Purkit [17] conducted a cross-sectional study on the 200 subjects while Paulinus et al [15], did a retrospective and prospective study of over 200 subjects. The collection of data offered by our study probably covers the most extensive age range with a large number of subjects in each gender and age group.…”
Section: Discussionmentioning
confidence: 99%
“…The current and voltage of the tube range 250-300 mAs and 120-150 kvp respectively were used for the cranial CT scans. Images were obtained in the axial plane with multiplanar reformatted sagittal and coronal images with the workstation software (vitrea version 6.9.2) at the respective point of measurement as previously reported by Paulinus et al 17 and Jain et al 18…”
Section: Image Acquisitionmentioning
confidence: 99%